2011
DOI: 10.1007/s00404-011-1882-1
|View full text |Cite
|
Sign up to set email alerts
|

Total laparoscopic hysterectomy in patients with previous abdominal surgery

Abstract: In our study, TLH can be performed successfully in patients with a history of abdominal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
3
4
1
Order By: Relevance
“…The prevalence of lower urinary tract injury during hysterectomy ranges from 0.30% to 1.35% and bladder injury is more common than ureter injury . The laparotomic conversion rate ranges from 0.60% to 6.97% . The prevalence of major complications in our study was consistent with previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence of lower urinary tract injury during hysterectomy ranges from 0.30% to 1.35% and bladder injury is more common than ureter injury . The laparotomic conversion rate ranges from 0.60% to 6.97% . The prevalence of major complications in our study was consistent with previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…6,7,21,22 The laparotomic conversion rate ranges from 0.60% to 6.97%. [23][24][25] The prevalence of major complications in our study was consistent with previous studies.…”
Section: Safety Of Tlh In Patients With Prior Cssupporting
confidence: 90%
“…The overall complication rate of 3.0% in the present study was lower than in previously conducted studies (5.7%–19.0%) [ 13 15 16 17 18 ]. The reason for the relatively low complication rate in this study is presumably because an experienced surgeon performed TLH.…”
Section: Discussioncontrasting
confidence: 79%
“…In the study conducted by Yada-Hashimoto et al (10), the complication rate was similar in both groups (6.8 and 5.4%, respectively), and no bladder, bowel, ureteral or vascular injuries were encountered. However, in our study, the complication rate was higher in Group 1 (4.1% and 0%, respectively); no bowel or vascular injuries were encountered, except 1 cases of ureteral injury in Group 1 which was detected on the third day by ureteroscopic examination after surgery and ureteroneocystostomy was conducted via the abdomen.…”
Section: Discussionmentioning
confidence: 68%
“…The reason for this difference in complication rate may be due to the small number of cases reported here which is not fully representative. Again, in the study conducted by Yada-Hashimoto et al (10), no statistical difference was reported in the TLH success rates in patients with and without a history of abdominal surgery. In that study, three patients with (6.8%) and two patients without (1.5%) a history of abdominal surgery converted to laparotomy.…”
Section: Discussionmentioning
confidence: 81%